Pekerja wanita Malaysia di sebuah kilang elektronik Singapura / Lok Swee Yen - Lok , Swee Yen (1990)
In between 1984 and 1985, Singapore encounter economic depression but by the middle of 1986, the economic condition was gradually restored from the recession and by 1987 encounter economic boom. According to the Singapore Economic Trend Report dated 1. 7. 1986, Singapore G.D.P increase from 1.8% in 1986 to 8.8% in 1987. All sectors especially the manufacturing sector have achieved high prestige. New investment also rekindled by the year 1986 and 1987, United States of America, Western Europe and Japan forms the major investor in Singapore industry. This resulted in vast increased of demand for Singapore electronics goods in western markets especially America and consequently Singapore electronic industrial boomed. International reputated electronic factory which invested in Singapore are Philip; Texas Instrument;Hewlett Packard; Thomson ; Seagate Technology ; Conner Peripherals; Matsushita ; Hitachi and Sanyo etc. The economic boom in Singapore resulted in shortage of labour and higher demand for foreign worker by the year 1987. As a result Singapore Government was faced to loosen up working permit on unskilled labour to attracted foreign workers especially Malaysia worker to work in the republic. Consequently since 1987 thousands of Malaysian women from Johore ; Malacca ; Negeri Sembilan ; Selangor ; Perak ; Pahang ; Penang and Ipoh etc. migrated to Singapore to work in electronic factories. Most of the Malaysian women are young aged 18 to 24 and have just finished their secondary school. Majority of the production operators work in Singapore electronic factory are women because girl are more capable in handling sophisticated and small electrical components. Hence a great number of Malaysian women works in electronic industries manufacturing semiconductor; radio and hifi; color television; video recorder; disk drive and computer. Realising the fact an increase number of Malaysian women working in electronic factories in Singapore so a research aimed at analyzing the working conditions, the pull factors and problems faced by them.